El caso fortuito o fuerza mayor y su incidencia en la terminación de la relación laboral. - Arias López, Angie Nayeli (2024)
This work is based on an investigative study of the fortuitous event or force majeure and its impact on the termination of the employment relationship, which seeks to resolve the problem that has arisen when terminating said relationship due to the aforementioned cause. taking into account that inconveniences are generated in the judicial field between employers and workers when the case is not applied correctly, since in this way rights and principles that are basic to labor law are violated. The Ecuadorian Civil Code defines a fortuitous event or force majeure as an unforeseen event that cannot be resisted, for example a shipwreck, earthquake, among others. Consistent with the Labor Code, which in its articles recognizes the fortuitous event or force majeure as a cause to terminate the individual employment contract, establishes said cause as a fortuitous event or force majeure as long as they make work impossible, defines the same as an extraordinary event that cannot be foreseen or that, being foreseen, cannot be avoided by the contracting parties. Through the information obtained from the surveys carried out, the hypothesis proposed in this research work can be determined, using the proper methodology and applying the objectives that have been proposed, the appropriate conclusions and recommendations will be reached. This work is structured, in chapter I, the problem, objectives and justification of the research are presented and formulated. In chapter II, the theoretical framework is explained, which is based especially on studying how the cause of a fortuitous event or force majeure affects the termination of an employment relationship, the effects it generates, among others. Chapter III presents a description and methodology of the work. Chapter IV details the results 4 obtained and concludes with the appropriate conclusions and recommendations. Keywords: Act of God, force majeure, employment relationship, causality, work.